2005
DOI: 10.1073/pnas.0409182102
|View full text |Cite
|
Sign up to set email alerts
|

A cortico-cortical mechanism mediating object-driven grasp in humans

Abstract: Humans and other primates demonstrate an exquisite ability to precisely shape their hand when reaching out to grasp an object. Here we used a recently developed transcranial magnetic stimulation paradigm to examine how information about an object's geometric properties is transformed into specific motor programs. Pairs of transcranial magnetic stimulation pulses were delivered at precise intervals to detect changes in the excitability of corticocortical inputs to motor cortex when subjects prepared to grasp di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
90
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 31 publications
14
90
0
Order By: Relevance
“…Several brain structures have been recently implicated in anticipatory force control including the cerebellum and the frontal and parietal cortices (Imamizu et al 2000(Imamizu et al , 2004Yamamoto et al 2002). A recent study has suggested, in particular, the importance of cortico-cortical projections in producing motor cortical outputs in relation to the properties of an object manipulated by the hand (Cattaneo et al 2005).…”
Section: Maintaining Rotational Equilibriummentioning
confidence: 99%
“…Several brain structures have been recently implicated in anticipatory force control including the cerebellum and the frontal and parietal cortices (Imamizu et al 2000(Imamizu et al , 2004Yamamoto et al 2002). A recent study has suggested, in particular, the importance of cortico-cortical projections in producing motor cortical outputs in relation to the properties of an object manipulated by the hand (Cattaneo et al 2005).…”
Section: Maintaining Rotational Equilibriummentioning
confidence: 99%
“…This results in motor evoked potentials (MEPs) whose sizes predict the differential muscle activation required to grasp different objects (Cattaneo et al, 2005). The facilitation is related to grasp preparation, because it is absent when subjects just look at the object, or prepare arbitrary hand movements with equivalent muscle patterns (Cattaneo et al, 2005;Prabhu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The corticocortical inputs facilitated by paired-pulse TMS over M1 are thought to include those from PMC activated by visual presentation of graspable objects (Ziemann et al, 1998;di Lazzaro et al, 1999;Cerri et al, 2003;Shimazu et al, 2004;Cattaneo et al, 2005;Prabhu et al, 2007). This results in motor evoked potentials (MEPs) whose sizes predict the differential muscle activation required to grasp different objects (Cattaneo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, these studies have revealed a precise pattern of cortical activation that is closely related to the muscles required to grasp a given object [31,7,35]. A few studies have also examined the effect of TMS on the finger forces in the pinch grasp.…”
Section: Introductionmentioning
confidence: 99%